MORFOLOGI MIKROPARTIKEL EKSTRAK KINANG DENGAN VARIASI WAKTU DAN SUHU PROSES ULTRASONIKASI - inka padya (P3M Institut Teknologi Pagar Alam, 2022)
Indonesia is a tropical country that has biodiversity and known as a storehouse of herbal plants. In general Indonesian people have healthy traditional habits, by consuming several mixtures of herbal ingredients, which is the habit of Nginang. Nginang consists of several ingredients mixed with herbal plants such as betel leaf, areca nut, whiting and gambier which are then mixed and chewed. The habit of Nginang is mostly done by parents and is less desirable because it has a strong flavor and smell. The composition of kinang has many benefits because it contains antioxidant and antibacterial compounds, so that further action is needed by making innovations. The innovation that can be done is by making kinang extract microparticles. Microparticles have a size of 1 – 1000 µm, microparticles can be an effective delivery system for the active substance and can release more than 80% of the active substance within 10 minutes. The manufacture of microparticles can use the ultrasonication process. The objective of this reaserch was to determine the effect of variations in time and temperature of the ultrasonication process on the morphology of the microparticles of kinang extract. The ultrasonication time variations used were 30 minutes, 60 minutes, 90 minutes, and 120 minutes. While the ultrasonication temperatures used are 50°C, 60°C, and 70°C. The results of the Scanning Electron Microscope (SEM) show that the resulting microparticles are not spherical or irregular. At 150 times magnification, the size of the microparticles ranged from ± 54 m to 700 m. Based on the results of physical characteristics, it can be proven that the microparticles with the best morphology are in the variation of the ultrasonication process with a time of 30 minutes and a temperature of 60°C.